Towards using memoization for saving energy in android - Rua, Rui (2019)
Over the last few years, the interest in the analysis of the energy consumption of Android applications has been increasing significantly. Indeed, there are a considerable number of studies which aim at analyzing the energy consumption in the Android ecosystem, such as measuring/estimating the energy consumed by an application or block of code, or even detecting energy expensive coding patterns or APIs. In this paper, we present an initial study of the impact of memoization in the energy consumption of Android applications. We compare implementations of 18 methods from different applications, with and without using memoization, and measure the energy consumption of both of them. The results show that using memoization can be a good approach for saving energy, since 13 of those methods decreased their energy consumption.